1997
DOI: 10.1111/j.1651-2227.1997.tb08910.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of full‐term infants fed an evaporated milk formula

Abstract: The objective of this prospective, cohort study was to compare the nutritional status of full-term infants who were fed human milk (BF, n = 29), formula (FF, n = 30) or evaporated milk formulae (EM, n = 30) for at least 3 months. Infants were seen at enrollment, 3 and 6 months, at which times a blood sample, diet record and anthropometric data were collected. Infants in the EM group received solids earlier (12 +/- 5 weeks) than did FF infants (15 +/- 4 weeks), and both were earlier than BF infants (19 +/- 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…The relatively low response rate provided sufficient data for a market assessment and dietary information about Canadian infants that is not available nor been reported elsewhere. The sample size is also considerably larger than followed in other Canadian studies [6][7][8][9][10][11]14]. Heinz Canada agreed to share this information in order to provide data on feeding patterns of Canadian infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low response rate provided sufficient data for a market assessment and dietary information about Canadian infants that is not available nor been reported elsewhere. The sample size is also considerably larger than followed in other Canadian studies [6][7][8][9][10][11]14]. Heinz Canada agreed to share this information in order to provide data on feeding patterns of Canadian infants.…”
Section: Discussionmentioning
confidence: 99%
“…This affects the introduction of complementary feeding, defined as "the period during which other foods or liquids are provided along with breast milk" [5]. Within Canada, there have been reports published on food intake patterns for infants in Vancouver [6], Ottawa [7], Quebec [8,9], Newfoundland [10] and New Brunswick [11], but a national survey is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that it would not be unreasonable to consider antioxidant supplements in early infancy at least for selected groups of breast-fed infants including those of multiple pregnancies or infants from low socioeconomic backgrounds. We know that formula-fed infants consume greater amounts of vitamins and minerals than are present in human milk (37,38) without any known untoward effects. Alternatively, mothers could be supplemented with additional antioxidant nutrients during pregnancy to enhance the endogenous ability of the infant at birth to cope with oxygen stress.…”
Section: Discussionmentioning
confidence: 99%
“…Debski et al (1992) showed differences of Se incorporation in cows'-milk protein from different regions of Poland. Besides lower bioavailability, compared with human milk, infant feeding with cows' milk will result in lower Se intakes due also to its lower Se concentration (Millar & Sheppard, 1972;Friel et al 1997). While breast milk has only half of the protein content of cows milk, breast-milk protein contains twice as much Se as cows' milk (Millar & Sheppard, 1972).…”
Section: Breast-feeding and The Infant's Selenium Statusmentioning
confidence: 99%